Cost-benefit analysis : financial and economic appraisal using spreadsheets - Campbell, Harry F., 1945-; Brown, Richard P. C., 1951- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
'Now in its third edition, Cost-Benefit Analysis has been updated, offering readers the perfect introduction to project, programme and policy appraisal using basic tools of financial and economic analysis. The key economic questions of any social cost-benefit analysis are: do the benefits of the project or policy exceed the costs, no matter how widely costs and benefits are spread, and irrespective of whether or not project impacts, such as environmental effects, are reflected in market prices? And which group or groups of individuals receive the benefits and which bear the costs? This book addresses these questions with an emphasis on putting the theory presented in the book into practice. This third edition has several attractive features: Readers are encouraged to develop their own skills by applying the tools and techniques of cost-benefit analysis to case studies and examples, including an analysis of a project which is developed throughout the book. The book emphasizes the use of spreadsheets which are invaluable in providing a framework for the cost-benefit analysis. A dedicated chapter provides guidance for writing up a report which summarizes the analysis which has been undertaken. New pedagogical features, including Technical Notes and Examples, have been added as an aid to readers throughout the text. An appendix provides fourteen additional case studies which can be developed in class or as assignment projects. This updated edition is an ideal text for a course on cost-benefit analysis where the emphasis is on practical application of principles and equipping students to conduct appraisals. It is also a useful handbook for professionals looking for a logical framework in which to undertake their cost-benefit analysis work'--
OCLC-licensed vendor bibliographic record.
Keywords: Cost effectiveness; Decision making; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Economics / Microeconomics; BUSINESS & ECONOMICS / Public Finance